Pengaruh Kualitas Produk, Kualitas Pelayanan Terhadap Keputusan Pembelian Di Foodcourt Le Garden PIM - Vinanda, Vinanda; Juwita, Ratna (Universitas Multi Data Palembang, 2024)
This research aims to see the effect of product quality and service quality on purchasing decisions at the Le Garden Palembang Indah Mall food court partially and simultaneously. The sample of this research is consumers who buy at the Le Garden Palembang Indah Mall Food Court totaling 398 respondents. Data analysis techniques use instrument feasibility tests, linear regression analysis, hypotension tests, R2 tests. This data was processed using IBM SPSS 25 software. The results of this research state that product quality and service quality have a partial and simultaneous positive and significant effect on purchasing decisions.